Machine learning and deep learning techniques for medical image recognition - Soufiene, Ben Othman; Chakraborty, Chinmay, 1984- (Boca Raton : Taylor and Francis, 2024)
"Machine Learning and Deep Learning Techniques for Medical Image Recognition comprehensively reviews deep learning-based algorithms in medical image analysis problems including medical image processing. It includes a detailed review of deep learning approaches for semantic object detection and segmentation in medical image computing, and large-scale radiology database mining. A particular focus is placed on the application of convolutional neural networks with the theory, and varied selection of techniques for semantic segmentation using deep learning principles in medical imaging supported by practical examples. The book offers important key aspects in the development and implementation of ML and DL approaches toward developing prediction tools and models and improving medical diagnosis and it teaches how ML and DL algorithms are applied to a broad range of application areas, including Chest X-ray, breast CAD, lung and chest, microscopy, and pathology and so forth. It also covers common research problems in medical image analysis and their challenges while focussing on aspects of deep learning and machine learning for combating COVID-19. It also includes pertinent case studies. This book is aimed at researchers and graduate students in computer engineering, artificial intelligence and machine learning, and biomedical imaging"--
Medical Image Detection and Recognition using Machine learning and Deep learning / Arun Anoop M, Karthikeyan P and Poonkuntran S -- Multiple lung disease prediction using x-ray images based on deep convolutional neural network / Nagarjuna Telagam, Nehru Kandasamy, Kumar Raja D R, Tharuni Gelli, D. Ajitha -- Analysis of Machine Learning and Deep Learning in Health Informatics, and its application / Gelli Tharuni, Challa Sri Gouri, D. Ajitha, Telagam Nagarjuna, Ben Othman Soufiene -- Automated Acute Lymphoblastic Leukemia Detection using Blood Smear Image Analysis / Chandan Kumar Jha, Arvind Choubey, Maheshkumar H. Kolekar, Chinmay Chakraborty -- Smart Digital Healthcare Solutions using Medical Imaging and Advanced AI Techniques / P Divyashree, Priyanka Dwivedi -- Efficient Lung diseases model Predictor toward fast prediction / Souid Abdelbaki, Hamroun Mohamed, Ben Othman Soufiene, Sakli Hedi -- Artificial intelligence used to recognize fetal plans based on ultrasound scans during pregnancy / Haifa Ghabri, Ben Othman Soufiene, Hedi Sakli -- The Artificial intelligence techniques for cancer detection from medical images / Rabiaa Tbibe, Ben Othman Soufiene, Chinmay Chakraborty, Sakli Hedi -- Handling segmentation and classification problems in deep learning for identification of Interstitial Lung Disease / Tapas Pal, Biswadev Goswami, Rajesh P Barnwal -- Computer Vision approaches in the Radiograph Images Analysis : A Targeted Review of Current Progress, Challenges and Future Perspective / Souid Abdelbaki, Ben Othman Soufiene, Sakli Hedi -- Deep Learning Method for Brain Tumor Segmentation / Marwen SAKLI, Chaker ESSID, Bassem BEN SALAH, Hedi SAKLI -- Face Mask Detection and Temperature Scanning for the Covid-19 Surveillance System based on deep learning models / Nagarjuna Telagam, D. Ajitha, Nehru Kandasamy, Ben Othman Soufiene -- Diabetic disease prediction using machine learning models and algorithms for early classification and diagnosis assessment / Aayush, Jawahar Sundaram, Devaraju S, Sujith Jayaprakash, Harishchander Anandaram, Manivasagan C -- Defeating Alzheimer, AI perspective from diagnostics to prognostic : literature summary / Iheb Elghaieb, Abdelbaki Souid, Ahmed Zouinkhi, Hedi Sakli.
Includes bibliographical references and index.
BME
English
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Image Processing, Computer-Assisted -- methods; Machine Learning